Studi Perbandingan Kemampuan Nannochloropsis sp. dan Spirulina sp. sebagai Agen Bioremediasi terhadap Logam Berat Timbal (Pb) [Comparative Study Of Ability Nannochloropsis sp. And Spirulina sp. As Agent Bioremediation Of Heavy Metal Plumbum (Pb) ] - Endang Dewi Masithah; Boedi Setya Rahardja; Tri Nadya Olyvia Kerin Hardianie (Faculty of Fisheries and Marine Universitas Airlangga, 2013)
Abstract Sea water is a component that interacts with the terrestrial environment, where the discharge of waste empties into the sea to the mainland. One of the most dangerous pollutants for human health is the heavy metal plumbum (Pb). Bioremediation offers a promising alternative method and the potential to reduce the concentration of heavy metals in water. Bioremediation is the application of biological processes to recover a contaminated place by using microorganisms. Biomass of algae Nannochloropsis sp. can be used as bioremediation of heavy metals because it has the ability adsorption caused the active cluster contained therein. In addition, Spirulina sp. thought to have the ability as an agent of bioremediation of heavy metal plumbum (Pb) because the proteins and polysaccharides are high. Information about uptake ability of heavy metal of plumbum (Pb) by Nannochloropsis sp. and Spirulina sp., in order to know how it compares to the ability of Nannochloropsis sp. and Spirulina sp. in absorbing the content of heavy metal plumbum (Pb). The method used in this study is the experimental method, the test T of SPSS analysis as the experimental design. Treatment given in the form of differences in the concentration of plumbum, which include, treatment A (Nannochloropsis sp. without the addition of plumbum), treatment B (Nannochloropsis sp. 0.9 ppm with plumbum concentrations), treatment C (Spirulina sp. without the addition of plumbum) and treatment D (Spirulina sp. with plumbum concentrations 0.9 ppm) of each treatment was repeated 5 times. The main parameters measured were real heavy metal plumbum (Pb) in water culture media Nannochloropsis sp. and Spirulinna sp. The results showed that Nannochloropsis sp. and Spirulina sp. able to absorb the heavy metals plumbum (Pb) so that it can be used as a bioremediation agent, where Spirulina sp. have higher ability in absorbing heavy metals plumbum (Pb) compared with Nannochloropsis sp